Liquid biopsy using extracellular vesicle–derived DNA in lung adenocarcinoma - In Ae Kim; Jae Young Hur; Hee Joung Kim; Seung Eun Lee; Wan Seop Kim; Kye Young Lee (Journal of Pathology and Translational Medicine, 2020)
Blood liquid biopsy has emerged as a way of overcoming the clinical limitations of repeat biopsy by testing for the presence of acquired resistance mutations to therapeutic agents. Despite its merits of repeatability and non-invasiveness, this method is currently only used as a supplemental test due to a relatively low sensitivity rate of 50%–60%, and cannot replace tissue biopsy. The circulating tumor DNAs used in blood liquid biopsies are passive products of fragmented DNA with a short half-life released following tumor cell death; the low sensitivity seen with liquid blood biopsy results from this instability, which makes increasing the sensitivity of this test fundamentally difficult. Extracellular vesicles (EVs) are ideal carriers of cancer biomarkers, as cancer cells secret an abundance of EVs, and the contents of tumor cell-originated EVs reflect the molecular and genetic composition of parental cells. In addition, EV-derived DNAs (EV DNAs) consist of large-sized genomic DNAs and tumor-specific oncogenic mutant DNAs. For these reasons, liquid biopsy using EV DNA has the potential to overcome issues arising from tissue shortages associated with small biopsies, which are often seen in lung cancer patients, and the biopsy product can be used in other diagnostic methods, such as epidermal growth factor receptor (EGFR) mutation testing and next-generation sequencing (NGS). A higher sensitivity can be achieved when EV DNAs obtained from bronchoalveolar lavage fluid (BALF) are used rather than those from blood. BALF, when obtained close to the tumor site, is a promising liquid biopsy tool, as it enables the gathering of both cellular and non-cellular fractions of the tumor microenvironment, and provides increased diagnostic sensitivity when compared to blood.